Endoscopic obstruction predominantly occurs in right-side colon cancer and endoscopic obstruction with tumor size ≤ 5 cm seems poor prognosis in colorectal cancer - Yu, Nong; Lin, Shuangming; Wang, Xiaojie; Hu, Guoxin; Xie, Run; Que, Zhipeng; Lai, Runsheng; Xu, Dongbo (Frontiers in Oncology, 2024)
Background Endoscopic obstruction (eOB) is associated with a poor prognosis in colorectal cancer (CRC). Our study aimed to investigate the association between tumor location and eOB, as well as the prognostic differences among non-endoscopic obstruction (N-eOB), eOB with tumor size ≤ 5 cm, and eOB with tumor size > 5 cm in non-elderly patients. Methods We retrospectively reviewed the clinicopathological variables of 230 patients with CRC who underwent curative surgery. The multivariable logistic regression model was used to identify risk factors for eOB. The association between eOB with tumor size ≤ 5 cm and disease-free survival (DFS) was evaluated using multivariate cox regression analysis. Results A total of 87 patients had eOB while 143 had N-eOB. In multivariate analysis, preoperative carcinoembryonic antigen (p = 0.014), tumor size (p = 0.010), tumor location (left-side colon; p = 0.033; rectum; p < 0.001), and pT stage (T3, p = 0.009; T4, p < 0.001) were significant factors of eOB. The DFS rate for eOB with tumor size ≤ 5 cm was significantly lower (p < 0.001) in survival analysis. The eOB with tumor size ≤ 5 cm (p = 0.012) was an unfavorable independent factor for DFS. Conclusions The patients with eOB were significantly associated with right-side colon cancer as opposed to left-side colon cancer and rectal cancer. The eOB with tumor size ≤ 5 cm was an independent poor prognostic factor. Further studies are needed to target these high-risk groups.